WACANA NASIONALISME NAJIB AL-KILANI: TELAAH ATAS NOVEL AL-NIDA AL-KHALID - Muhandis Azzuhri (IAIN Pekalongan, 2009)
Nationalism discourse is an amazing social invention in human history, at least in the latest century. There are no social spaces in the earth that are free from this ideology influence. Without nationalism, human history line could be very different. NajÄ«b al-KÄ«lanÄ« as an Egyptian novelist discussed it in his novel, al-NidÄ al-KhÄlid (1969).